STRENGTHENING FUTURE ORIENTATION, ENTREPRENEURIAL ORIENTATION, AND ENTREPRENEURIAL COMPETITION TOWARDS THE RESILIENCE OF FEMALE STUDENT - Sriayudha, Yayuk; Octavia, Ade; Enggrani Fitri , Lucky; Dylan Al Muzzaky, Ahmad (Journal of Business Studies and Management Review, 2025)
Female’s entrepreneurship is increasingly recognized as a vital economic force in various countries. Female students engaged in entrepreneurship play a crucial role in societal development and the economic growth of a nation. The active involvement of higher education institutions through a series of policies serves as a milestone in the advancement of entrepreneurship among students. This study aims to : (1). Analyze the impact of future orientation and entrepreneurial competition on entrepreneurial orientation and entrepreneurial resilience among female students, (2). Analyze the influence of entrepreneurial orientation on entrepreneurial resilience among female students, and (3). Analyze the effect of future orientation and entrepreneurial competition on entrepreneurial resilience among female students, with entrepreneurial orientation as a mediating variable. This research employs a descriptive quantitative approach. The study population consists of female students at Universitas Jambi, with a sample of 300 respondents drawn from eight faculties. Data collection was conducted using a questionnaire with perception statements measured on a five-point Likert scale. Data analysis was performed using Structural Equation Modeling (SEM) with PLS3 as the analytical tool. The findings indicate that future orientation and entrepreneurial competition significantly influence entrepreneurial orientation and entrepreneurial resilience among female students in Universitas Jambi. Additionally, entrepreneurial orientation serves as a mediating variable in the research model. This study is expected to contribute to strengthening entrepreneurship among female students and enhancing their entrepreneurial capabilities. Furthermore, the research aims to reinforce the theory of entrepreneurial resilience and provide recommendations for higher education institutions to increase the number of entrepreneurial competitions as platforms for students to develop their entrepreneurial skills.